Glacial geomorphology of Newfoundland, Canada - Sophie L. Norris; Jennifer Organ; Arthur S. Dyke; Taryn Neligan; Cameron C. Stanton; Kelsey Strickland; John C. Gosse (Journal of Maps)
We present a synthesis of glacial geomorphology comprising Newfoundland and the surrounding continental shelf. During the last glaciation, this region was encompassed by the Newfoundland Ice Cap that coalesced with the Laurentide Ice Sheet and extended to the continental shelf edge. The subglacial geomorphic signal of terrestrial and marine portions of this ice sheet has been mapped using aerial photography, satellite imagery, SRTM DEMs, multibeam bathymetric data and onshore field mapping over the last 50 years. Here, we build on this, digitizing ∼146,380 features identified in published literature. Using newly available digital elevation data and multibeam bathymetric data, we identify ∼38,550 new features, such as undocumented ice thrust, crevasse and esker ridges and meltwater channels. This updated geomorphological map provides a record of paleo landforms over Newfoundland, enabling future efforts to reconstruct the dynamics, timing and erosion history of ice advance and retreat during the last glacial period..